2014
DOI: 10.1016/j.soilbio.2013.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in soil microbial communities during primary succession

Abstract: Article (refereed) -postprintCutler, Nick A.; Chaput, Dominique L.; van der Gast, Christopher J. 2014. Long-term changes in soil microbial communities during primary succession.Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. little is known about long-term (decades-centuries) structural changes in these communities. 22T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 54 publications
6
48
1
Order By: Relevance
“…Along with our findings, it has to be mentioned that, we only found differences among the differently treated sites in the fourth year of the experiment. This finding suggests, that natural development of fungal community in soils, feed-back among vegetation and soil community jointly interacted with the applied treatment, and required a longer time to express in the vegetation composition (Wang et al, 2011;Cutler et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Along with our findings, it has to be mentioned that, we only found differences among the differently treated sites in the fourth year of the experiment. This finding suggests, that natural development of fungal community in soils, feed-back among vegetation and soil community jointly interacted with the applied treatment, and required a longer time to express in the vegetation composition (Wang et al, 2011;Cutler et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…It triggers this effect by reducing competition among species that facilitate coexistence in the critical phase of community development (Mariotte et al, 2013). Furthermore there are evidences showing that, not only the vegetation can change during succession, but simultaneously soil fungal community, suggesting a sensitive feed-back between plants and soil fungi ( Sikes et al, 2012, Cutler et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In a dry environment, microbial succession may lag behind plant succession, but plant and microbes demonstrate a similar succession pattern (Lozano et al, 2014). Previous studies reported that bacteria and fungi evolved along different trajectories under various conditions, such as secondary succession in a restored ecosystem (Banning et al, 2011;Li et al, 2013a), shrub encroachment (Yannarell et al, 2014), and the primary succession of lava flows (Cutler et al, 2014) and glacier soils (Brown and Jumpponen, 2014). The different succession patterns were determined by the range of microbial physiologies, dispersal ability, and assembly pattern .…”
Section: Discussionmentioning
confidence: 99%
“…Yannarell et al (2014) found that both bacterial and fungal communities demonstrated significant variation along transects spanning the prairie-shrub-forest continuum, but their predominant patterns were different. Cutler et al (2014) showed that the composition of plant communities was significant for fungal communities, but less relevant for bacterial communities during primary succession on an 850-year chronosequence of lava flows. In retreating glaciers, the presence of plants was important in bacterial successional dynamics, but played a minor role in those of fungi (Brown and Jumpponen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies show differences in communities from soils with contrasting treatments Garbeva et al 2008;Geisseler and Scow 2014;de Quadros et al 2012;Zhalnina et al 2013). In non-agricultural systems there is evidence for the development of distinct bacterial communities selected over centuries (Cutler et al 2014;Jangid et al 2011) and fungal communities over decades (Hogberg et al 2014) with soil pH a major factor in microbial community structure at continental, landscape and field scale (Fierer and Jackson 2006;Griffiths et al 2011;Zhalnina et al 2015). Soil factors including pH and C: N ratio had a greater influence than land use on bacterial communities in Netherlands soil (Kuramae et al 2011), although these factors will also be influenced by agricultural land use.…”
Section: Introductionmentioning
confidence: 99%